Liability for contamination of halal restaurant facilities by consumers in Indonesia - Farisi, Gusti Muhammad Reyhan; Fatoni, Rifky Hamdan; Al Ghofsah, M. Salman Al Farisi (Journal of Halal Product and Research, 2025)
The contamination of product facilities in halal-certified restaurants in Indonesia is an important concern in the context of product assurance.  One of the viral incidents occurred in a restaurant that has been certified as halal. However, a consumer, either intentionally or due to negligence, brought non-halal food and drinks from outside and used the restaurant's tableware. This action raises concerns about the potential contamination of the restaurant's halal facilities, which may jeopardize halal certification and Muslim consumer confidence. Based on the background of this problem, this study aims to analyze whether the actions of consumers who pollute halal product facilities in restaurants can be categorized as Tortious Acts and to analyze the legal protection for the restaurant (producer) against the actions of these consumers. This research employs a legal research method with a legislative approach, examining the regulation and a conceptual approach to liability and Tortious Acts. The results showed that consumer liability for pollution of restaurant halal facilities based on Article 1365 Burgerlijk Wetboek as the "Indonesian Civil Code” depends on the fulfillment of the elements of a tort, namely, one of which is a violation of the law, which is not strictly regulated in Law No. 33 of 2014 concerning Halal Product Assurance (Jaminan Produk Halal, hereinafter the JPH Law). Meanwhile, the JPH Law emphasizes the responsibility of producers to ensure the product's halalness. This study concludes that there is a need for regulatory changes related to consumer responsibility in maintaining halal product facilities and a more specific legal protection mechanism for restaurants against pollution of halal facilities by consumers   Keywords: Liability, Contamination, Defilement, Serving Tools, Halal